AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN ENGLISH FOREIGN LANGUAGE CLASSROOM AT JUNIOR HIGH SCHOOL SMP Kr. CREDO KOLONGAN - Lamasigi, Chrysto; Tuerah, Ignatius J.; Rombepajung, Paula (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this research was to find speaking anxiety existence and determined the factor caused speaking anxiety on 2nd grade junior high school. The research was conducted at SMP Kr. Credo kolongan Kec. Kombi with all the 2nd grade students’ as the respondent. In order to accomplish this research, the writer collected all the data from all the students when this research was held. The writer used Foreign Language Classroom Anxiety Scale (FLCAS) and translated to Indonesian as the instrument on this research. The findings based on the research was there are speaking anxiety at 2nd grade students’ caused by communication apprehension with 46.1% as the factor which is influent students’ speaking ability in English Foreign Language Classroom